(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : Ocular foreign body can affect at any age as well as in both genders. Foreign body introduction in eye leads to various disturbances which can create significant health related problem. The study of the ocular foreign body gives unparalleled opportunities in reducing morbidity as well as for realizing significant savings for both financial as well as human terms. Material and Method: This prospective study was conducted in ophthalmology department at of Krishna hospital, Karad, Hundred patients with ocular foreign bodies were included in study with consideration of inclusion and exclusion criteria. Results : A study of 100 subjects showed that incidence of extraocular foreign bodies is very common compared to intraocular foreign bodies. Amongst that, corneal foreign bodies found to be have highest incidence. Commonest foreign body observed -iron particle (43%) and thorn/vegetative material (38%). Average age-40 years. Males are having higher incidence than females. Average interval between incident and intervention – 2.6 days (day 0 to day 10). Amongst the affected population, farmers and welders are maximum in number. Conclusion : Though incidence of intraocular foreign body is very less, it has bad prognosis in relation with vision as well as progresses to endophthalmitis. Early visit to ophthalmologist showed better prognosis and thus visual outcome specially in cases of vegetative foreign body in which delayed treatment lead to further complications.